ICTs and enterprise: conceptual proposals to generate indicators for the information society (Journal of Information Systems and Technology Management, 2006)
This paper is an attempt to deepen the reflection on how Information and Communication Technologies (ICTs) diffusion among firms takes place. It adds to author's previous works on the different strategies adopted by small and medium enterprises (SMEs) in Argentina in order to adopt ICTs. The paper is focused in the stylization of the different stages along the evolutive path while incorporating these tools and identifying the factors that influence its dynamics, with special attention to costs. The paper is also an attempt to make progress in the description of the paths or ways through which ICTs can improve firms' performance. Four alternatives are pointed out, named "Economies through Information": automation, access to information, learning and innovation processes facilitation and reduction of transaction costs. Authors try to make operable some notions frequently used by other authors interested in these issues and to formulate some hypothesis which still need further elaboration, but which will probably stimulate and inspire the debate around these matters.